Long-term transportation noise exposure and incidence of ischaemic heart disease and stroke: a cohort study. Issue 4 (25th February 2019) - Pyko, Andrei; Andersson, Niklas; Eriksson, Charlotta; de Faire, Ulf; Lind, Tomas; Mitkovskaya, Natalya; Ögren, Mikael; Östenson, Claes-Göran; Pedersen, Nancy L; Rizzuto, Debora; Wallas, Alva Käte; Pershagen, Göran
Abstract : Background: There is limited evidence from longitudinal studies on transportation noise from different sources and development of ischaemic heart disease (IHD) and stroke. Objectives: This cohort study assessed associations between exposure to noise from road traffic, railway or aircraft and incidence of IHD and stroke. Methods: In a cohort of 20 012 individuals from Stockholm County, we estimated long-term residential exposure to road traffic, railway and aircraft noise. National Patient and Cause-of-Death Registers were used to identify IHD and stroke events. Information on risk factors was obtained from questionnaires and registers. Adjusted HR for cardiovascular outcomes related to source-specific noise exposure were computed using Cox proportional hazards regression. Results: No clear or consistent associations were observed between transportation noise and incidence of IHD or stroke. However, noise exposure from road traffic and aircraft was related to IHD incidence in women, with HR of 1.11 (95% CI 1.00 to 1.22) and 1.25 (95% CI 1.09 to 1.44) per 10 dB Lden, respectively. For both sexes taken together, we observed a particularly high risk of IHD in those exposed to all three transportation noise sources at≥45 dB Lden, with a HR of 1.57 (95% CI 1.06 to 2.32), and a similar tendency for stroke (HR 1.42; 95% CI 0.87 to 2.32). Conclusion: No overall associations were observed between transportation noise exposure and incidence of IHD or stroke. However, there appeared to be an increased risk of IHD in women exposed to road traffic or aircraft noise as well as in those exposed to multiple sources of transportation noise.